2015
DOI: 10.1038/srep17185
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of stem/progenitor cell cycle using murine circumvallate papilla taste bud organoid

Abstract: Leucine-rich repeat-containing G-protein coupled receptor 5-expressing (Lgr5+) cells have been identified as stem/progenitor cells in the circumvallate papillae, and single cultured Lgr5+ cells give rise to taste cells. Here we use circumvallate papilla tissue to establish a three-dimensional culture system (taste bud organoids) that develops phenotypic characteristics similar to native tissue, including a multilayered epithelium containing stem/progenitor in the outer layers and taste cells in the inner layer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
74
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 65 publications
(74 citation statements)
references
References 60 publications
0
74
0
Order By: Relevance
“…To follow the generation of taste cells in real time, we generated organoids from transgenic mice that express green fluorescent protein (GFP) under the control of the promoters of Trpm5 (type II cell marker) 22, 23 or Gad1 (type III cell marker) 24, 25 . We previously succeeded to generate taste organoids directly from isolated circumvallate papilla tissue 12 , and others have reported that dissociated lingual epithelial cells can generate organoids 26 . However, most of these organoids appear to be non-taste organoids, as taste cell markers could not be detected 26 .
Figure 1Tracking the generation of taste cells in cultured organoids.
…”
Section: Resultsmentioning
confidence: 99%
“…To follow the generation of taste cells in real time, we generated organoids from transgenic mice that express green fluorescent protein (GFP) under the control of the promoters of Trpm5 (type II cell marker) 22, 23 or Gad1 (type III cell marker) 24, 25 . We previously succeeded to generate taste organoids directly from isolated circumvallate papilla tissue 12 , and others have reported that dissociated lingual epithelial cells can generate organoids 26 . However, most of these organoids appear to be non-taste organoids, as taste cell markers could not be detected 26 .
Figure 1Tracking the generation of taste cells in cultured organoids.
…”
Section: Resultsmentioning
confidence: 99%
“…The circadian clock synchronizes the timing of cell division cycles with 1:1 or 1:2 coupling ratios in different subpopulations of cells, depending on their inherent CCTs (Figure 4C). Intriguingly, these synchronized cell division cycles emerge from heterogeneous CCTs with a multimodal distribution as a result of the coupling (Figure 3; Aihara et al, 2015; Nagoshi et al, 2004). Importantly, we also uncover WNT-mediated intercellular coupling between circadian rhythms and the cell cycle in 3D enteroids.…”
Section: Discussionmentioning
confidence: 99%
“…Sutherland and colleagues termed their Chinese hamster V79 lung cell aggregates "multicellular spheroids" and further described the three typical zones found in most of these 3D spherical cultures: an inner necrotic layer, an intermediate zone of quiescent cells as well as an outer stratum of proliferating cells [18]. However, depending on the application, small spheroids can be generated to avoid a necrotic core [19]. Spheroids are mostly made by the hanging drop method [20,21] or by the use of non-adherent U-bottom shaped plates [22].…”
Section: Spheroidsmentioning
confidence: 99%